[tex]\boxed {24._{\boxed {a)}} }[/tex] [tex]\left(\sqrt{2}-1\right)\left(\sqrt{3}+1\right) =[/tex]
[tex]\\\boxed{\left(a+b\right)\left(c+d\right)=ac+ad+bc+bd}[/tex]
[tex]=\sqrt{2}\sqrt{3}+\sqrt{2}\cdot \:1-1\cdot \sqrt{3}-1\cdot \:1[/tex]
[tex]=\sqrt{6}+\sqrt{2}-\sqrt{3}-1[/tex]
[tex]\boxed {b)}[/tex] [tex]3\left(3-\sqrt{5}\right)+2\left(1+\sqrt{5}\right) =[/tex]
[tex]=9-3\sqrt{5}+2\left(1+\sqrt{5}\right)[/tex]
[tex]=9-3\sqrt{5}+2+2\sqrt{5}[/tex]
[tex]=11-3\sqrt{5}+2\sqrt{5}[/tex]
[tex]=11-\sqrt{5}[/tex]